The effect of glutathione spraying to reduce the negative effect of water stress on the yield of three genotypes of Cucumis sativus L. - Al-shammari, Aziz Mahdi Abd; Mohammed, Hussien Aziz; Abdulhasan, Waleed Fouad (Journal of agricultural, environmental and veterinary sciences, 2020)
The experiment was conducted during spring season 2017 in the experimental station of the Department of Horticulture and Landscape, College of Agriculture Diyala University, Iraq. In order to know the best genetic makeup for the cucumber plant in terms of production and to determine the best irrigation level for this crop without damaging the production amount and to determine the best concentration of glutathione in reducing the harmful effects of water stress in the cucumber quotient, As the study included three factors, namely: three genotypes of the cucumber, which are Demmy (V1) and Ghazeer (V2) and Wesam (V3), and second: two levels of irrigation are Complete irrigation 100% (I1) of field capacity and 50% of complete irrigation (I2). Third, spray glutathione in three concentrations (0, 50, 100) mg L-1 and its symbol (G0, G1, G2). The experiments were arranged in a Split-Split Plot Design in R.C.B.D. and with three replicates. The results of the study showed the superiority of plants for genotyping and decoration in the diameter of the fruit and the yield of one plant and the total yield in hectares, as it reached 3.436cm, 1.686 kg plant-1 and 53.97tons h-1, respectively, while the composition exceeded the prolific length of the fruit with an average of 19.83cm. The level of irrigation exceeded 100% significantly in terms of the number of fruits, the weight of the fruit and the yield of one plant and the total yield in hectares, as it reached 11.65 fruit plants-1, 142.3g, 1.717 kg plant-1 and 54.94 tons h-1. The results showed the role of glutathione in improving the ability of the plant to adapt to the presence of water stress, as the levels of spraying glutathione exceeded 50 and 100 mg L-1 without a significant difference between them on the comparison treatment (G0) and in order of the characteristics of the number of fruits (11.38 and 11.75 plant fruits-1) The weight of the fruit (141.9 and 144.7 g), the length of the fruit (19.84 and 19.88 cm), the diameter of the fruit (3.452 and 3.500 cm) and the yield of one plant (1.688 and 1.722 kg Plant-1) and the total yield (54.03 and 55.12 tons h-1). The triple interaction between genotypes, irrigation levels and levels of glutathione spraying showed a significant effect on the yield of cucumber plants, as treatment V3I1G2 was superior to the number of fruits (13.27 fruit plant-1), fruit weight (148.7 g), fruit diameter (3,655 cm), and single plant yield (1.888 kg Plant-1) and the total yield (60.41 tons h-1), while treatment V2I1G1 was outperformed in the length of the fruit (21.00 cm).